Netrin-1 Ameliorates Blood-Brain Barrier Impairment Secondary to Ischemic Stroke via the Activation of PI3K Pathway - Yu, Jian; Li, Chenguang; Ding, Qiao; Que, Jiali; Liu, Kejia; Wang, Haoyue; Liao, Songjie (Frontiers in Neuroscience, 2017)
Secondary impairment of blood-brain barrier (BBB) occurs in the remote thalamus after ischemic stroke. Netrin-1, an axonal guidance molecule, presents bifunctional effects on blood vessels through receptor-dependent pathways. This study investigates whether netrin-1 protects BBB against secondary injury. Netrin-1 (600 ng/d for 7 days) was intracerebroventricularly infused 24 h after middle cerebral artery occlusion (MCAO) in hypertensive rats. Neurological function was assessed 8 and 14 days after MCAO, and the permeability of BBB in the ipsilateral thalamus was detected. The viability of brain microvascular endothelial cells was determined after being disposed with netrin-1 (50ng/mL) before oxygen-glucose deprivation (OGD). The role of netrin-1 was further explored by examining its receptors and their function. We found that netrin-1 infusion improved neurological function, attenuated secondary impairment of BBB by up-regulating the levels of tight junction proteins and diminishing extravasation of albumin, with autophagy activation 14 days after MCAO. Netrin-1 also enhanced cell survival and autophagy activity in OGD-treated cells, inhibited by UNC5H2 siRNA transfection. Furthermore, the beneficial effects of netrin-1 were suppressed by PI3K inhibitors 3-Methyladenine and LY294002. Our results showed that netrin-1 ameliorated BBB impairment secondary to ischemic stroke by promoting tight junction function and endothelial survival. PI3K-mediated autophagy activation depending on UNC5H2 receptor could be an underlying mechanism.